Integration of chemical fertilizer with biological products on growth and production of rice during wet season - Sana, Megha; Jana, Kalyan; Mondal, Ramyajit; Mondal, Krishnendu; Banerjee, Hirak (ORYZA-An International Journal of Rice, 2020)
The influence of different biological products (JumpStart, Bolt GR, Ratchat, Azospirillum and phosphate solubilizing bacteria/PSB) in conjunction with recommended dose of chemical fertilizer (RDF) were evaluated with one control (RDF only) on wet season rice cv. Satabdi (IET 4786) during wet season of 2017 and 2018 at Instructional Farm under Bidhan Chandra Krishi Viswavidyalaya, West Bengal. The experiment was laid down in randomized complete block design (RCBD) with seven treatment combinations replicated thrice. The results showed that tallest plants (103.5 cm) with maximum dry matter accumulation (889.8 g/m2) were observed in RDF +Bolt GR @ 10 kg/ha treated plots. The same treatment augmented panicle number/m2 (248.5), panicle weight (3.95g), filled grains/panicle (126.1), grain (4.22 t/ha) and straw yields (5.83 t/ha); being statistically at par with RDF + Azospirillum @ 2 kg/ha. Yield increase was to tune of 8.18 to 23.39 %. Significant and positive associations of grain yield with traits like plant height, dry matter accumulation, effective tillers/m2, panicle weight and filled grains/panicle were noticed. Bolt GR @ 10 kg/ha in conjunction with recommended dose of chemical fertilizer (RDF) recorded significantly higher N and K uptake in grain and straw. While greater P uptake in both grain and straw was noticed with Azospirillum @ 2 kg/ha and PSB @ 2 kg/ha. Combined application of JumpStart @ 0.83 ml/kg seed resulted in significantly greater fungal population in post-harvest soil. The actinomycetes and bacterial population were improved with soil applied Azospirillum @ 2 kg/ha and Bolt GR @ 10 kg/ha, respectively. Hence, we suggested a mixture of recommended dose of chemical fertilizer (RDF) with either Bolt GR @ 10 kg/ha or soil applied Azospirillum @ 2 kg/ha to exploit not only growth and yield of rice but also improvement of soil microbial populations for rice productivity in Gangetic alluvial soil of West Bengal.